Anxiety-Related Coping Styles, Social Support, and Internet Use Disorder - Jung, Sonja; Sindermann, Cornelia; Li, Mei; Wernicke, Jennifer; Quan, Ling; Ko, Huei-Chen; Montag, Christian (Frontiers in Psychiatry, 2019)
Objective: The Internet can offer a seemingly safe haven for those being disappointed by relationships in the “offline world”. Although the Internet can provide lonely people with opportunities to seek for help and support online, complete withdrawal from the offline world comes with costs. It is discussed if people can even become “addicted” to the Internet. Of note, meanwhile many researchers prefer the term Internet Use Disorder (IUD) instead of using the term Internet addiction. To illustrate the importance of one’s own social network supporting a person in everyday life, we investigated, to our knowledge for the first time, how social resource in terms of quality and quantity might represent a buffer against the development of IUD. Furthermore, anxiety coping related personality traits are investigated as a further independent variable likely impacting on the development of IUD as a person variable. Method: In the present work, N = 567 participants (n =164 males and n = 403 females; Mage: 23.236; SDage = 8.334) filled in a personality questionnaire assessing individual differences in cognitive avoidant and vigilant anxiety processing, ergo traits describing individual differences in everyday coping modes. Moreover, all participants provided information on individual differences in tendencies towards IUD, the perceived quality of one’s own social support and the size of the social network (hence a quantity measure). Results: Participants with larger social networks and higher scores in social support reported the lowest tendencies towards IUD in our data. A vigilant coping style was positively correlated with tendencies towards IUD, whereas no robust associations could be observed between a cognitive avoidant coping style and tendencies towards IUD. Hierarchical linear regression underlined an important predictive role of the interaction term of vigilance in the ego-threat scenario and social support. Conclusion: The current study yields not only support for the hypothesis that the size of one’s own social network as well as the perceived quality of one’s own social support in everyday life presents a putative resilience factor against developing IUD. It also supports the approach that special coping strategies are needed to make use of the social support offered.